Perspectives on connected and augmented human care. Nursing in the digital age (Salud, Arte y Cuidado, 2024)
This article explores how digitalization, connectivity and artificial intelligence are transforming the field of health and nursing. It highlights the opportunities for these advances to improve quality and safety of care, as well as their potential to reduce the financial costs of the health system and the intangible costs for patients. Through the integration of technologies such as home monitoring, predictive studies and interoperable information systems, access to care, continuity of treatment and personalization of care for users can be improved. Nursing plays a crucial role in this transformation, using digital technologies to monitor, follow-up and remotely care for patients. I am on the ground optimizing case management and interprofessional communication, which also reduces errors and working time. Digital health training at universities is essential to prepare nurses for the future, guaranteeing more personalized and humane care.